Early cutaneous Langerhans cell histiocytosis. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
Cutaneous Langerhans cell histiocytosis has a variable prognosis. The latter is influenced by the presence or absence of extracutaneous lesions, the time of appearance, the distribution, number, shape and size of skin lesions. When skin lesions are added to hepatic, bone or other organ lesions, the prognosis worsens. On the other hand, when only skin lesions are present at onset, the prognosis is the better the earlier the beginning, when the lesions are not distributed in seborrheic sites, are few in number and can be counted, and when they have variable morphology – nodules, papules, pustules of various color and size – (1). In the present case the lesions were only cutaneous; although non congenital, they were acquired in the first week of life, distributed in seborrheic sites but also in other locations, had variable dimensions and could be counted. Careful clinical-laboratory monitoring is mandatory in this case (2).